Optimasi Formula Pempek dengan Penambahan Pasta Isolat Protein Kedelai Berdasarkan Preferensi Konsumen - Bayu Ikhlasul Amal; Joko Hermanianto; Dase Hunaefi (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2023)
Pempek is one of the traditional foods of South Sumatra which is a processed food made from fish and tapioca flour. The chewy texture of pempek is very popular among consumers, but the addition of too much tapioca flour can make pempek has a hard texture. One alternative to improve the texture of pempek is using isolate soy protein (ISP). This study aims to obtain the optimum formulation of pempek added with isolate soy protein based on consumer preferences and identify the ideal attributes sensory of pempek. The method used in this research is the preparation of the formulation with the RSM using the Design-Expert 13 application, profiling attributes with FGD, testing physical texture with Texture Analyzer, hedonic test, data analysis, CATA and hedonic tests for the optimum formulation, and proximate test for the selected formulation. Based on the results of the analysis, two formulations of pempek were selected from 17 formulas of pempek with the highest desirability values, 0.84 (sample 179) and 0.74 (sample 952). Based on the results of the CATA test, sample 952 has the closest sensory attributes to ideal pempek based on consumer preferences with favorite sensory attributes being artificial aroma (MSG), umami taste, and chewy texture.